Constraints to increasing agricultural productivity in Nigeria: A review - Phillip, Dayo; Nkonya, Ephraim M.; Pender, John L.; Oni, Omobowale Ayoola (International Food Policy Research Institute, 2009)
This paper reviews the constraints hindering growth of agricultural productivity in Nigeria by providing an overview of the policy environment that affects agricultural productivity, establishing how the policy environment affects productivity improvement, and proposing lessons relevant for future research and policymaking to promote productivity growth in Nigeria